Association between pharyngeal residue and posterior oral spillage with penetration and aspiration in Stroke - Santos, Rarissa Rúbia Dallaqua Dos; Sales, André Vinicius Marcondes Natel; Cola, Paula Cristina; Ribeiro, Priscila Watson; Jorge, Adriana Gomes; Peres, Fernanda Matias; Dantas, Roberto Oliveira; Silva, Roberta Gonçalves Da (Sociedade Brasileira de Fonoaudiologia, 2014)
PURPOSE: This study aimed at showing association between the posterior oral spillage and pharyngeal residue with tracheal aspiration and/or laryngeal penetration in stroke. METHODS: Clinical cross-sectional retrospective multicenter study. The study included 63 videofluoroscopic tests of post-ischemic stroke individuals and oropharyngeal dysphagia data of the three reference centers providing care for patients with dysphagia (43 men and 20 women; age range: from 40 to 90 years). These individuals were divided into two groups. Group I consisted of 35 participants with the presence of penetration and/or laryngotracheal aspiration, and Group II consisted of 28 individuals with no penetration and/or aspiration. Videofluoroscopic swallowing test results were analyzed to divide the groups, and the presence of posterior oral spillage and pharyngeal residue was observed. RESULTS: No association was found between the groups with posterior oral spillage (χ2=1.65; p=0.30; φ2=0.02), but there was statistical difference for the association between pharyngeal residue (χ2=12.86; p=0.003; φ2=0.20) and the groups. CONCLUSION: There is an association between pharyngeal residue and penetration with tracheal aspiration in post-stroke individuals..

OBJETIVO: Este estudo teve por objetivo verificar a associação entre a ocorrência de escape oral posterior e a presença de resíduos faríngeos com penetração laríngea e/ou aspiração laringotraqueal no acidente vascular encefálico (AVE). MÉTODOS: Estudo clínico transversal, retrospectivo e multicêntrico. Foram incluídos neste estudo 63 exames videofluoroscópicos de indivíduos pós-AVE isquêmico e disfagia orofaríngea do banco de dados dos serviços de três centros públicos de referência no atendimento do indivíduo disfágico, sendo 43 do gênero masculino e 20 do gênero feminino, faixa etária variando de 40 a 90 anos. Estes foram divididos em dois grupos. O Grupo I foi composto por exames de 35 indivíduos com presença de penetração e/ou aspiração laringotraqueal e o Grupo II, por exames de 28 indivíduos com ausência de penetração e/ou aspiração. Foram analisados exames de videofluoroscopia da deglutição para dividir os grupos e observou-se a presença de escape posterior e resíduos faríngeos. RESULTADOS: Não houve associação entre os grupos com o escape oral posterior (χ2=1,65; p=0,30; φ2=0,02), porém houve associação entre resíduos faríngeos (χ2=12,86; p=0,003; φ2=0,20) e os grupos. CONCLUSÃO: Diante dos resultados obtidos, concluiu-se que há associação entre a presença de resíduos faríngeos com a ocorrência de penetração com aspiração laringotraqueal em indivíduos pós-AVE.
Associação entre presença de resíduos faríngeos e escape oral posterior e a ocorrência de penetração e aspiração no Acidente Vascular Encefálico
Keywords: Transtornos de deglutição; Avaliação; Acidente vascular cerebral; Aspiração respiratória; Deglutition disorders; Evaluation; Stroke; Respiratory aspiration